Legal Analysis of Legal Protection for Doctors in Reporting Patient Safety Incidents to Improve the Quality of Health Services - Bintartho, Agung; Nasser, M; Sutrisno (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2025)
Study This give deep insight about protection law for doctor in practice medical based on Constitution Number 17 of 2023 concerning Health and its derivatives . Focus main study This is For highlight challenges and dilemmas faced by doctors in operate his profession , including problem protection law for doctor in report incident safety patients , with hope can increase quality service health in a way overall , which at the moment This Still referring to the Minister of Health Regulation no. 11 of 2017 concerning safety patient . One of the the most crucial aspect in study This is analysis to Article 189 of the Health Law , which regulates importance effective communication between House sick and patient . Article This underline obligation doctors and institutions health For build transparent , clear , and interest - oriented communication patient . In context this , good communication can reduce potential misunderstanding and avoidance problem the law that arises consequence lack of information or ambiguity in service medical . Besides that , service model health offered by the Law This put forward not quite enough answer together between provider service health and patients . In matter This , Article 310 emphasizes that the patient also has obligation For active participate in the treatment process , providing the necessary information , as well as follow instructions medical with well , as part from safety patient . Responsibility answer together This No only aim For protect profession medical from potential demands law , but also creates environment service more optimal health , where both , doctor and patient , can each other support For reach the best results . Through study this , it is hoped There is improvement quality communication in practice medicine and more Lots understanding about regulated rights and obligations in The Health Law , which finally can repair connection between doctors and patients , as well as increase quality service health in a way overall